Adopting the evaluation of the electronic performance of the teaching staff and the extent of its impact on the diversity of scientific activities - Heba Loqman Ameen; Duha Khalid Abdul-Rahman Al-Malah; Dhuha Saad Ismael (Genius Publishing Group, 2021)
The evaluation of university performance in the past years has produced a huge leap in the field of using electronic technologies and the transformation of electronic management, as the university administration is no longer looking for statement and information only, but has expanded to include technically diverse dimensions, especially in how to achieve efficiency and effectiveness in documenting human resources information. This study sought to clarify the role of university performance evaluation in achieving development in highlighting scientific and administrative competencies, and the study relied on the views of a sample of those included in the evaluation of university performance in the research sample, as the research problem was embodied by the question (Is there a moral correlation between the electronic evaluation of university performance and the diversity of scientific activities?), and whether there is a role for the electronic evaluation elements in improving scientific quality. The study aimed to analyze the relationship and show the impact between the teachers ’electronic performance evaluation and the extent to which they are assured of their efficiency and effectiveness in developing the scientific direction at the university. Therefore, a scheme must be created and tested to arrive at an image that reflects the relationship between the study variables. The researchers adopted a hypothetical model that was built after reviewing and analyzing the relevant literature under the main hypothesis
Keywords: documentation; Electronic form for performance evaluation; standards and grades; scientific activity